The Formal Design and Analysis of Distributed Data-Processing Systems - Fitzwater, D.R. (University of Wisconsin-Madison Department of Computer Sciences, 1977)
The research proposal is to support the development of the "science" behind software engineering in order to ensure required system properties, to compare current software engineering techniques, to develop specification for new design and analysis tools, and to demonstrate the practicality of the "science". A hierarchical design schema will be developed within which formal representations and analyses can be defined and the required solutions can be found. Since "worst-case" problems are generally impossible to solve, sufficient design laws or constraints will be developed to ensure solvability of the critical problems.